LATENT DIMENSIONS OF CONATIVE CHARACTERISTICS OF TOP SENIOR BASKETBALL PLAYERS - Joško Sindik; Joško Vukosav (Sport Scientific And Practical Aspects, 2025)
The aim of this study was to investigate the latent structure in the set of conative characteristics of Croatian elite male senior basketball players. We have examined the purposeful sample of 74 basketball players, who played in 9 teams of A-1 Croatian Men’s Basketball League, with the corresponding measuring instruments. The factor analysis results showed that space of conative characteristics and perceived group cohesion can be satisfying explained with four factors. The construct validity of psychological measurement instruments, applied on a sample of basketball players, is well-confirmed